Persuasion strategies: use of negative forces in scam e-mails - Chitchanok Naksawat,; Songyut Akkakoson,; Chek, Kim Loi (Penerbit Universiti Kebangsaan Malaysia, 2016)
The 21st century globalisation strongly influences the world as a result of highly improved technology and communications which made it possible for everyone involved to have equal access to a global market and information exchange via English. As a result, electronic communication has become part of the present-day multinational professionals of all fields who work daily in front of their digital monitors. At times, these professionals may receive Nigerian 419 scam e-mails in which fraudsters target victims to make advance payments for financial gains that do not materialise. In these e-mails, situations in which persuasion techniques are intertwined are well crafted. As a result, the victim who is susceptible to the offer is more likely to respond and be lured into losing money eventually. The present study, consequently, analysed a corpus of 50 Nigerian 419 scam e-mails through a textual analysis to examine language aspects in terms of persuasion strategies fraudsters used as a compelling force to achieve their communicative purposes of lures and deceits. The study has revealed two major types of deceptive techniques which are used in combination, namely framing-rhetoric triggers, disguised as the traditional genre of electronic communications and human weakness-exploiting triggers, intended as incitement of recipients' emotions. Finally, the paper includes not only pedagogical suggestions for business English teachers when implementing classroom activities, but also warnings for either pre-experienced or experienced business professionals in relation to interpreting the unknown e-mails' messages they receive with great caution.